Stance and stance-support strategies in English argumentative writing by Malaysian undergraduate writers - Lee, Geok Imm (2017)
This study investigated how Malaysian undergraduate writers (106 first and 129 final year undergraduates who were referred to as junior and senior undergraduate writers) expressed their stance and stance-support in their argumentative writing. IELTS writing band descriptors were used to examine the stance and stance-support statements (under the component of task response in IELTS) in their essay writing. A correlation using Pearson correlation coefficient analysis was also done to investigate the task response and writing performance. The frequency of use for the stance-support strategies in their essays was counted and analyzed based on a checklist of stance-support strategies (Chandrasegaran & Kong, 2006). Furthermore, an awareness test was conducted to investigate their awareness of the stance-support strategies. A correlation was also done between their awareness of the stance-support strategies and use of these strategies. Their argumentative essays were further examined to determine the lexico-grammatical features used for expressing stance, based on Biber’s (2006) framework. The results showed that the senior undergraduate writers were able to express their stance more clearly and provide better stance support (as task response) in their argumentative writing, as indicated in their higher mean scores based on IELTS writing band descriptors. The analysis using Pearson correlation showed significant correlations between the task response and writing performance for both groups of writers. However, the component of task response had a greater influence on the writing performance of only the junior undergraduate writers.In terms of the frequency of use of stance-support strategies, the senior undergraduate writers demonstrated more use of most of these strategies.The strategies most frequently used by both groups of writers were the writer’s use of elaboration and examples. In contrast, the writer’s use of analogy was the least used strategy. Regarding the awareness test, the senior undergraduate writers showed a significantly greater awareness of stance-support strategies. Both groups of writers were aware of the writer’s use of personal opinion, followed by the use of factual statement, observation of events and use of reference to source of authority. They were least aware of strategies like the writer’s hypothesized situation based on a claim and the writer’s appeal to the reader’s emotions.Pearson correlation analysis revealed that there was a significant correlation between the writer’s awareness and use of stancesupport strategies for the junior undergraduate writers, but not for the senior undergraduate writers. As for the use of lexico-grammatical features, the senior undergraduate writers showed more use of lexico-grammatical features for specific strategies. The most frequently used lexico-grammatical features by both groups of writers were modal verbs and prepositional phrases. Their least used lexico-grammatical feature was stance complement clause controlled by adjectives. In conclusion, this study has demonstrated that the undergraduate writers’ abilities to state and support their stance can still have room for improvement. Therefore, writing instructors can use these findings as useful resources for developing suitable writing tasks for argumentative essays.The checklists of stance-support strategies and lexicogrammatical features based on this study can be used in ESL writing courses.